EAP AND ACADEMIC DISCOURSE: MEDIATING ELABORATED CODE IN A CLIL TYPE TEACHER EDUCATION - Lankiewicz , Hadrian (Neofilolog, 2020)
The aim of this paper is to relate the concept of ESP to the idea of Content and Language Integrated Learning (CLIL) to work out a platform for the conceptualization of academic language as a context-reduced means of communication (Bernstein, 1971; 1999). Subsequently, the concept of talk-types (Moate, 2011) will be presented as a way of counteracting language de-contextualization and engendering restructuring of knowledge and the language itself. Theoretical considerations will be supported with the presentation of research on classroom interaction. It is aimed at highlighting how expert language is mediated in content learning with types of classroom talk and how the process of languaging (Swain, 2006a) facilitates both “taming” (Lankiewicz, 2013b) of the elaborated code and acquisition of expert knowledge.